Cultural frames of early childhood education leadership - Hannele Roponen; Elina Fonsén; Tuulikki Ukkonen-Mikkola; Raisa Carpelan (Journal of Early Childhood Education Research)
This qualitative case study examined leadership culture in early childhood education (ECE) amid change. Causal layered analysis (CLA) was employed to gain a comprehensive understanding of the leadership culture as experienced by the staff. The aim of the study was to create parallel and complementary views on leadership culture and their systemic drivers. The data consisted of focus group interviews (N = 4) including a total of seven ECE teachers and eight ECE nurses from one Finnish ECE center. The study presents three cultural frames of ECE leadership culture: the storm, the labyrinth, and the golden age. Based on these, a transformative future vision was created for the development of ECE leadership: leadership culture as an orchestra. The study revealed the importance of dialogue between different levels of leadership and support for the professional agency of staff through inclusive structures and processes. The findings suggest that leaders need to build a shared understanding of various leadership roles and the artifacts of leadership culture, which are crucial for managing organizational culture. The study provides an opportunity for critical reflection on the future qualification requirements for ECE leaders and the cultural expectations related to ECE as a female-dominated field. Additionally, the methodological approach of this study enriches leadership research in ECE and therefore offers theoretical implications as well.